2011
DOI: 10.1124/dmd.111.040048
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Modeling of the Effect of an Sodium-Glucose Cotransporter Inhibitor, Phlorizin, on Renal Glucose Transport in Rats

Abstract: ABSTRACT:A pharmacokinetic and pharmacodynamic (PK-PD) model for the inhibitory effect of sodium-glucose cotransporter (SGLT) inhibitors on renal glucose reabsorption was developed to predict in vivo efficacy. First, using the relationship between renal glucose clearance and plasma glucose level in rats and both the glucose affinity and transport capacity obtained from in vitro vesicle experiments, a pharmacodynamic model analysis was performed based on a nonlinear parallel tube model to express the renal gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…As shown in Fig. 2, there was no significant effect of phlorizn on HCT116 cell attachment at doses known to inhibit SGTL2 [7].…”
Section: Cell Culturementioning
confidence: 93%
“…As shown in Fig. 2, there was no significant effect of phlorizn on HCT116 cell attachment at doses known to inhibit SGTL2 [7].…”
Section: Cell Culturementioning
confidence: 93%
“…The glucose concentrations in plasma and urine samples were determined using a Glucose CII-Test Wako kit (Wako Pure Chemical Industries, Ltd., Osaka, Japan). The PK-PD data of phlorizin was cited from a previous report (Yamaguchi et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…f u was calculated as the mean value of three experiments. The f u values of tofogliflozin (Suzuki et al, 2012) and phlorizin (Yamaguchi et al, 2011) were cited from previous reports. PK-PD Studies of SGLT Inhibitors in Rats.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have reported particular PK-PD models to evaluate the UGE of SGLT2 inhibitors, [13][14][15][16][17][18][19] only four have adopted the mechanism-based PK-PD models: the PK-PD model for tofogliflozin in rats 16,17) and the PK-PD model of dapagliflozin and canagliflozin in humans. 18,19) In these studies, the investigators adopted the physiological construction of the proximal tubule in the kidney and the kinetics of competitive SGLT1/2 inhibition in their PK-PD model and successfully described the time course of UGE.…”
Section: -4)mentioning
confidence: 99%